Determinan Kinerja Keuangan Syariah Daerah Provinsi Sumatera Utara dengan Belanja Modal sebagai Variabel Moderating - Agnesia, Inge; Ridwan, M; Batubara, Maryam (el Buhuth: Borneo Journal of Islamic Studies, 2023)
This study aims to determine the effect of General Allocation Funds (DAU), Special Allocation Funds (DAK), Regional Taxes, and regional levies on Regional Sharia Financial Performance Efficiency with regional expenditure moderation variables. This research method uses a quantitative method approach with the help of the Eviews program version 9. This research uses secondary data originating from the Budget Realization Report (LRA) and the Regional Revenue and Expenditure Budget Realization Report of the District/City Government of North Sumatra Province. This research was conducted in North Sumatra Province and the time of the research was carried out in stages from October 2021 to August 2022. The results showed that (1) general allocation funds did not have a significant and negative effect on regional sharia finances, (2) regional taxes had an insignificant and negative effect on regional sharia finances, (3) regional levies have no significant and positive effect on regional sharia finances, (4) General Allocation Funds have no significant and positive effect on regional sharia finances through capital expenditure as a moderating variable, (5) special allocation funds have no significant and negative effect on regional sharia finances through capital expenditures, (6) regional taxes do not have a significant and positive effect on regional sharia finances through capital expenditures as a moderating variable, and (7) regional levies have an insignificant and positive effect on regional sharia finances through capital expenditures as a moderating variable.